Risk factors of atherosclerosis during systemic therapy targeting vascular endothelial growth factor - Študentová, Hana; Indráková, Jarmila; Petrová, Pavla; Kamínek, Milan; Kalábová, Hana; Šrámek, Vlastislav; Adam, Tomáš; Melichar, Bohuslav (Oncology letters, 2016)
The aim of the present study was to examine the changes in intima-media thickness (IMT) and myocardial perfusion in association with other laboratory risk factors for atherosclerosis in patients treated with therapy that targeted vascular endothelial growth factor (VEGF). IMT, myocardial perfusion and laboratory risk factors of atherosclerosis were studied in 58 patients with metastatic colorectal carcinoma or metastatic renal cell carcinoma prior to and at 3-monthly intervals during anti-VEGF treatment. Compared with the pretreatment IMT, the results indicated that the IMT was consistently increased during therapy in the two patient groups. Patient blood pressure and concentration of troponin T increased transiently. An increase in the concentration of high-density lipoprotein cholesterol and decrease in the concentrations of C-reactive protein and homocysteine were also observed. Novel myocardial ischemia was evident in individual patients. In conclusion, anti-VEGF therapy affects the laboratory risk factors of atherosclerosis and results in an acceleration of atherosclerosis, as demonstrated by increased IMT.
Keywords: intima-media thickness; atherosclerosis; biomarkers; single-photon emission computed tomography